Insights from Students on the Use of Asynchronous and Synchronous Approaches during Digital Learning in Thailand’s Primary Schools - Muhammad, Ribeh Najib (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2024)
The outbreak of Covid-19 necessitated a rapid shift in educational paradigms worldwide. With physical classrooms rendered inaccessible, educators and students turned to distance learning as the new norm. This study investigates the effectiveness of two prominent e-learning strategies: synchronous learning (facilitated by platforms like Zoom) and asynchronous learning (centered on video materials). The primary objective was to discern which approach better supported students in their educational journey while they remained confined to their homes during quarantine. The pandemic disrupted traditional educational models, prompting institutions to adapt swiftly. Distance learning emerged as a lifeline, but questions lingered about the most effective methods. This research aimed to address this gap by comparing synchronous and asynchronous learning strategies. The investigation took place in multiple schools across Thailand, where students had been navigating remote learning. A questionnaire with Likert scale questions assessed students’ perceptions as well as interviews and open-ended responses to provide deeper insights. It turns out that students favored synchronous learning due to its ease of communication. Zoom sessions allowed direct interaction with teachers and peers although both approaches effectively delivered content, but asynchronous learning lacked real-time feedback. Moreover, synchronous learning provided a structured environment, while asynchronous learning allowed flexibility.